A Look at Women's Representation in Indonesia After the 2019 Election - Mardiah, Adinda Rabiki; Nurwijayanti, Septi (Universitas Muhammadiyah Yogyakarta, 2025)
Women's representation in parliament certainly has an important role. As users of regulations, women also have the same political rights as men. Women's representation has a critical role in increasing community welfare because women, such as problems regarding reproductive health and violence, better understand various issues. However, women's representation in Indonesia, unfortunately, has not reached 30% of the total parliamentarians. Affirmative action in Indonesian politics has been carried out since the 2009 election. Unfortunately, until the 2019 election, women's representation in parliament only reached 21%. The aims of this research is to investigate the post-reform elections and women's representation in parliament after the 2019 elections developed. This research uses normative juridical research that will analyze regulations regarding elections, accompanied by secondary data. The initial result of this study is that the lack of women's representation in Indonesia is caused by various factors, such as political parties' understanding of women's representation as an administrative requirement only and patriarchal culture that is too deeply rooted in Indonesian society that contributes to hindering women's representation in parliament.